If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -4n = 16 Solving 4m + -4n = 16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4n' to each side of the equation. 4m + -4n + 4n = 16 + 4n Combine like terms: -4n + 4n = 0 4m + 0 = 16 + 4n 4m = 16 + 4n Divide each side by '4'. m = 4 + n Simplifying m = 4 + n
| 10x+6y=-23 | | 6(2a+10)=5(a+5)5 | | 10h-3=70 | | w+16=8w | | 4x+4z=6 | | 9x^2=3y | | 2m^3+5m^2-18m-45=0 | | 32+5*32=192 | | 5n*n=7-n | | -4(y+3)=-6y-26 | | -4v+20=7(v-5) | | 3x(h+1)+2=20 | | x+17=-(2x-8) | | 2y^2+8y+216=0 | | -2t+4-16=-12-19t | | 9x-3(x-6)=-6 | | Y=13-5x | | -4+20=7(v-5) | | (x^2+4)((x+2)(x-2))=0 | | 9x-3(a-6)=-6 | | -2t+4-16t=-12-19t | | (x+2)(x+2)(x+2)(x-2)=0 | | 2(w+3)-5w=-24 | | 4u+6=-18 | | 5n^2-38-15n=0 | | -5w=-6w-7 | | -3t-6-2t=-6-5t | | 15x-2-6x= | | 5ln(x+1)=30 | | 2a-3a=20 | | (3X)3=24 | | (y+4)(3y-2)=-y-14 |